Collaborative governance in handling covid-19 for elderly social services - Kurnia Nur Fitriana (Universitas Negeri Yogyakarta, 2022)
In 2050, Indonesia will enter an ageing population of around 21.1% of the total population. Life expectancy has increased significantly despite having a high vulnerability to neglect due to elderly poverty in the COVID-19 pandemic. This condition encourages the need for inclusive service design to promote health and empower ageing in collaborative governance. In this paper, the author presents a study on how collaborative governance interventions in inclusive services for long-term elderly care in the COVID-19 pandemic. As a representation of national strategic research, this research uses research and development designs through interviews, observations, focus group discussions, analysis of elderly data documentation in 2021. The findings show collaborative governance in inclusive services during the COVID-19 pandemic can increase social resilience and empowerment of the elderly. Although, the elderly mortality rate during the COVID-19 pandemic is still high, there is a strengthening of stakeholder participation, social inclusion, and long-term policy support. So, the adoption of collaborative governance in inclusive services can improve the social welfare of the elderly in the long term care post-COVID-19. The implication is that it is necessary to strengthen the role capacity and participation of stakeholders at the local level based on social capital.